A phase 2a randomized controlled study to evaluate the pharmacokinetic, safety, tolerability and clinical effect of topically applied Umeclidinium in subjects with primary axillary hyperhidrosis. (7th November 2017) - Nasir, A.; Bissonnette, R.; Maari, C.; DuBois, J.; Pene Dumitrescu, T.; Haddad, J.; Yamaguchi, Y.; Dalessandro, M.
Abstract: Background: Hyperhidrosis is a common medical condition which can have a significant impact on quality of life. Umeclidinium (UMEC) is a long‐acting muscarinic antagonist (LAMA) developed as a dermal formulation. Objectives: This 2‐week, double‐blind, randomized, vehicle‐controlled study evaluated systemic exposure, safety and tolerability of topically administered UMEC in subjects with primary axillary hyperhidrosis. Clinical effect was a secondary objective, measured by gravimetry and the hyperhidrosis disease severity scale (HDSS). Vehicle was included to evaluate safety. Methods: Twenty‐three subjects were randomized to either 1.85% UMEC ( N = 18) or vehicle ( N = 5) once daily. Results: Measurable plasma concentrations were observed in 78% of subjects after the treatment. Nine subjects (50%) on UMEC and two subjects (40%) on vehicle reported AEs, most commonly application site reactions. At Day 15, seven subjects (41%) in UMEC and two subjects (40%) in vehicle had at least a 50% reduction in sweat production. Eight subjects (47%) in UMEC and one subject (20%) in vehicle had at least a two‐point reduction in HDSS. No comparisons of treatment arms were planned prospectively. Conclusions: The measurable exposure, acceptable safety and preliminary clinical activity observed in this proof‐of‐concept study suggest the potential clinical utility of topical UMEC in subjects with axillary hyperhidrosis.